2016
DOI: 10.3892/ol.2016.5019
|View full text |Cite
|
Sign up to set email alerts
|

Promoter methylation and downregulated expression of the TBX15 gene in ovarian carcinoma

Abstract: Abstract. TBX15 is a gene involved in the development of mesodermal derivatives. As the ovaries and the female reproductive system are of mesodermal origin, the aim of the present study was to determine the methylation status of the TBX15 gene promoter and the expression levels of TBX15 in ovarian carcinoma, which is the most lethal and aggressive type of gynecological tumor, in order to determine the role of TBX15 in the pathogenesis of ovarian carcinoma. This alteration could be used to predict tumor develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
(30 reference statements)
2
15
0
Order By: Relevance
“…Normally, either a high or a low level of methylation should have been observed because the proportion of tumor cells in our samples was greater than 70%. This observation had already been made for analyses of methylation on a single gene by our group but also by others [ 27 , 28 ]. However, our study of 41 genes indicates that this phenomenon is quite general.…”
Section: Discussionsupporting
confidence: 62%
“…Normally, either a high or a low level of methylation should have been observed because the proportion of tumor cells in our samples was greater than 70%. This observation had already been made for analyses of methylation on a single gene by our group but also by others [ 27 , 28 ]. However, our study of 41 genes indicates that this phenomenon is quite general.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, the corresponding upstream and downstream regions were located in a target gene, TBX15 . It has been demonstrated that TBX15 plays a vital role in multiple cancers, such as non–small cell lung cancer (Carvalho et al, 2013), thyroid cancer (Arribas et al, 2015), and ovarian carcinoma (Gozzi et al, 2016), and especially has been proved to be a methylation marker of prostate cancer (Kron et al, 2012). Moreover, Chelbi et al (2011) identified a region located in the distal promoter of the TBX15 that was differentially methylated and suggested that TBX15 might be involved in the pathophysiology of placental diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the association of TBX15 and cancer was demonstrated by the detection of breast cancer tissue-specific down-regulation of TBX15 , suggesting the use of TBX15 expression as a biomarker to facilitate accurate diagnosis and prognosis or as a predictive marker for treatment efficiency [ 28 ]. Further, the TBX15 promoter is hypermethylated in histological subtypes of ovarian cancer, and the methylation levels and expression of TBX15 inversely correlate [ 29 ]. Thus, hypermethylated TBX15 may serve as a potential biomarker for early detection of the induction and progression of ovarian cancer [ 29 ].…”
Section: Discussionmentioning
confidence: 99%